Reconfiguração de redes de distribuição de energia elétrica para minimização de perdas técnicas - Ezequiel Campos Pereira (2014)
Power losses are intrinsic to the process of generation, transmission and distribution of electricity and they must be minimized in order to guarantee the system´s efficiency. In the electric distribution, companies implement strategies to minimize such losses. One of these, the grid reconfiguration which is becoming important due to the process of grid automation with the progressive use of the Intelligent Eletronic Devices (IEDs) that allow remote operation. The nature of the reconfiguration problem is combinatory, non-differentiable and non-linear. In this work, the approach to the problems solution was based on the use of evolutionary algorithms to minimize power losses, dealing with technical and operational system constraints, such as voltage level, ampacity and grid radial arrangement. The approach has used several open-source power flow softwares to evaluate the grid configurations proposed. The developed optimization methodology was based on the differential evolution algorithm and it was applied to minimize the power loss from feeders. The proposed methodology was tested with benchmark grids found in the scientific literature, as well as, real feeders from Cemig Distribution company. The obtained results were compared with those from the literature, demonstrating that the developed methodology is promising and provides good results.